Fibre-direction strain measurement in a composite ply under quasi-static tensile loading using Digital Volume Correlation and in situ Synchrotron Radiation Computed Tomography. (October 2020) - Schöberl, E.; Breite, C.; Melnikov, A.; Swolfs, Y.; Mavrogordato, M.N.; Sinclair, I.; Spearing, S.M.
Abstract: Digital Volume Correlation (DVC), in concert with in situ Synchrotron Radiation Computed Tomography (SRCT), has been applied to Carbon-Fibre Reinforced Polymers (CFRPs) under quasi-static tensile loading. DVC represents a relatively novel tool for quantifying full-field volumetric displacements and implicit strain fields. The highly anisotropic and somewhat regular/self-similar microstructures found in well-aligned unidirectional (UD) materials at high volume fractions are shown to be intrinsically challenging for DVC, especially along the fibre direction. To permit the application of DVC to displacement and/or strain measurements parallel to the fibre orientation, the matrix was doped with a sparse population of sub-micrometre barium titanate particles to act as displacement trackers ( i.e. fiducial markers). For the novel materials systems we have developed, measurement noise is considered along with the spatial filtering intrinsic to DVC data processing. Compared to volume images acquired through Micro-focus Computed Tomography (µCT), hold-at-load artefacts are mitigated through scan times on the order of seconds using SRCT, as opposed to hours. Instances of individually fractured fibres evolving into clusters of breaks are presented, together with the associated strain redistribution (imaged at a voxel resolution of 0.65 µm). It is shown that the distance over which strain is recovered in the broken fibres not only increases with the applied force, but also with the number of broken fibres, delineating aspects of the load shedding phenomenon. The study demonstrates that unprecedented, mechanistically-consistent three-dimensional (3D) strain measurements may be made in relation to fibre failure events, that can be used to validate micromechanical models for predicting UD tensile failure. We believe this work presents the first application of DVC to the SRCT imaging of failure in CFRPs, achieving significantly higher resolution than reported previously within the literature.